Histamine aggravated levothyroxine-induced cardiomyopathy in guinea pigs - Hu Hui-Juan; Dai De-Zai; Shen Yong-Ming (Acta Pharmacologica Sinica, 2016)
AIM: To study effects of histamine on cardiomyopathy. METHODS: Cardiomyopathy model was developed in guinea pig by i.p. levothyroxine 0.5 mg.kg-1.d-1 for 10 d. Langendroff's hearts were perfused. ECG and contractile force were recorded. Histamine (5 micrograms) was given by intra-aortic injection. Histamine content of coronary venous effluent was determined fluorometrically. RESULTS: Attack of histamine on cardiomyopathy was severer than that in normal hearts. Tachycardia was more prominent; atrioventricular conduction block occurred earlier; decrease in coronary flow was more marked. Uptakes of histamine were 37% in the model and 19% in the normal hearts (P < 0.01). CONCLUSION: Histamine aggravated levothyroxine-cardiomyopathy.